Maternal care gaps; a study on ANC visit patterns and the reported challenges to prenatal care access in public sector hospitals of Rawalpindi District. - Bilal Sadiq; Hussain, Aqib; Sibgha Arshad Chudhry; Sakina; Mehreen Noor; Khaula Noreen (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Maternal and Child Health (MCH) is a critical area of focus globally due to its profound impact on the well-being of both mother and child. Owing to lack of proper MCH services, Maternal Mortality remains alarmingly high with many pregnant women succumbing to complications during and after pregnancy. Antenatal care (ANC), as a crucial component of maternal and child health (MCH), is one of the four pillars of safe motherhood recommended by the WHO. Pregnant mothers face various barriers that significantly hinder their ANC visits including social, cultural, economic, and geographical challenges. Given the lack of detailed regional data on ANC in Pakistan, particularly in Rawalpindi district, this study aims to assess the frequency of ANC visits and identify the barriers women face in accessing antenatal healthcare in the city. Objectives: To determine the frequency of ANC visits and to assess the reported barriers to ANC, as well as to establish the association between ANC visits and the reported barriers among pregnant women. Materials and Methods: A descriptive quantitative cross-sectional study was conductedin the Obstetrics and Gynecological Department of Tertiary Care Hospitals of Rawalpindi district with 348 pregnant women following their delivery either through SVD or C-section. For data collection a self-structured questionnaire was designed, consisting of socio-demographic profile, previous obstetric history, ANC visit patterns and reported barriers to ANC access.Data collection technique was one-on-one interview. Written informed consent was taken and confidentiality of the study participants was maintained. Data was entered and analyzed on SPSS version 26. Descriptive and inferential statistics were applied; p value of less than 0.05 was set as significant Results: The mean age of study participants was 28.26. ANC coverage was 97.7% out of which 79.9% received minimum 4 ANC visits while only 25% received recommended 8 ANC visits .Of the total participants, 84.8% delivered through C-section whereas the 15.2% via SVD. Among the barriers, lack of money for cost associated with transportation (p=0.015), education level of husband (p=0.042), employment status of the husband(p=0.032), language barrier with healthcare provider(p=0.010) and residence in urban areas(p=0.017) significantly influenced women’s ability to access ANC visits. Additionally lack of awareness among pregnant women appeared to be statistically significant in affecting ANC visits (with a p-value of 0.00). Conclusions: This study indicates that a considerable number of study participants received a minimum number of 4 ANC visits in Rawalpindi District. However, there is a need to address some major factors hindering the standard ANC visitations including limited awareness and geographic difficulties. Maternal health outcomes can be improved by addressing these issues and enhancing ANC services at the grass root level of Basic Health Units and Rural Health Centers to spare the population from the struggles of visiting tertiary care hospitals from distant areas. MESH keywords: Antenatal Care, Frequency, Barriers.